Analysis of the Influence of Knowledge Acquisition on Employee Loyalty with Spirituality as A Mediating Variable Through Religious Culture (Islamic Dress and Yaumi Charity) - Cindy Clara Sella; Awan Kostrad Diharto; Riska Anggraeni (Publikasi Indonesia, 2025)
The aim of this study was to evaluate how Knowledge Acquisition impacts employees' loyalty to spirituality, mediated through religious culture, which includes Islamic clothing and yaumi charity. Quantitative methods were used to obtain data from 85 employees of BMT XYZ, which were analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results of the study show that the acquired Knowledge Acquisition has a positive and significant effect on religious culture, spirituality, and employee loyalty. Spirituality also serves as a mediator through religious culture, strengthening the relationship between knowledge gained and employee loyalty. These results show that religious values and experiential learning are essential to create a harmonious work environment and increase employee loyalty in Sharia-based companies.